Evaluation of Bcl-2 as a marker for chronic kidney disease prediction in cats - Pila, Pattiya; Chuammitri, Phongsakorn; Patchanee, Prapas; Pringproa, Kidsadagon; Piyarungsri, Kakanang (Frontiers in Veterinary Science, 2023)
Chronic kidney disease (CKD) is a frequent condition in elderly cats. Bcl-2 is linked to kidney disease through the processes of apoptosis and fibrosis. The purpose of this study is to examine Bcl-2 levels in CKD and clinically healthy age-matched cats in order to evaluate the relationship between Bcl-2 levels, signalment, and blood parameters in cats with CKD. The circulating levels of Bcl-2 were determined using an immunoassay in twenty-four CKD cats and eleven clinically healthy age-matched cats by the utilization of the general linear model (GLM), Pearson correlation, principal component analysis (PCA), ROC curves, the Cox hazard model, and Kaplan–Meier survival analysis. These were all conducted in order to explore Bcl-2 levels and their connection with other variables. The Bcl-2 immunohistochemical intensity was graded in each glomerulus and tubulointerstitium. McNemar's test was performed in order to compare the expression of Bcl-2 in the two renal tissue sites. The circulating Bcl-2 of CKD cats was significantly lower than those of clinically healthy age-matched cats (P = 0.034). The presence of circulating Bcl-2 (P < 0.01) and the severity of CKD (P = 0.02) were both linked with the survival time of cats with CKD. The area under the curve (AUC) of Bcl-2 for detection of CKD was 0.723. In cats, decreased circulating Bcl-2 was associated with increased blood BUN, creatinine levels, and CKD severity. Bcl-2 protein expression was reduced in the renal tissues of CKD cats as the disease progressed, resulting in a decrease in their survival time. This study demonstrated that Bcl-2 may be effective in diagnosing feline CKD.